Viscosity and Structural Investigation of High-Concentration Al2O3 and MgO Slag System for FeO Reduction in Electric Arc Furnace Processing - Youngjae Kim; Dong-Joon Min (Metals, 2021)
In the present study, the viscosity of the CaO–SiO2–FeO–Al2O3–MgO slag system was measured for the recovery of FeO in the electric arc furnace (EAF) process using Al dross. Considering the MgO-saturated operational condition of the EAF, the viscosity was measured in the MgO-saturated composition at 1823 K with varying FeO and Al2O3 concentrations. An increase in the slag viscosity with decreasing temperature was observed. The activation energy was evaluated, and the change in the thermodynamically equilibrated phase was considered. The changes in the aluminate structure with varying FeO and Al2O3 concentrations were investigated by Fourier-transform infrared spectroscopy, which revealed an increase in the [AlO4] tetrahedral structure with increasing Al2O3 concentration. Depolymerization of the aluminate structure was observed at higher FeO concentrations. The Raman spectra showed the polymerization of the silicate network structure at higher Al2O3 concentrations. By associations between the silicate and aluminate structures, a more highly polymerized slag structure was achieved in the present system by increasing the Al2O3 concentration.